Methodology and system of selection of athletes in highly coordinated sports - Khaydarov, U. R. (Proximus Journal of Sports Science and Physical Education, 2024)
Today, the level of the highest sports achievements is so high that people with incomparable potential for this sport can approach them, and even more surpass them.Selection for sports remains one of the most pressing and unresolvedproblems in our country. Mistakes made during the selection process can manifestthemselves several years later and negate all the work of the coach and the athlete. Children and teenagers are left without the opportunity to show their motor skillsabilities in a certain sport.